2023
DOI: 10.1101/2023.12.13.571345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AAGGG repeat expansions trigger RFC1-independent synaptic dysregulation in human CANVAS Neurons

Connor J. Maltby,
Amy Krans,
Samantha J. Grudzien
et al.

Abstract: Cerebellar ataxia with neuropathy and vestibular areflexia syndrome (CANVAS) is a late onset, recessively inherited neurodegenerative disorder caused by biallelic, non-reference pentameric AAGGG(CCCTT) repeat expansions within the second intron of replication factor complex subunit 1 (RFC1). To investigate how these repeats cause disease, we generated CANVAS patient induced pluripotent stem cell (iPSC) derived neurons (iNeurons) and utilized calcium imaging and transcriptomic analysis to define repeat-elicited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…A recent study reported that pathogenic AAGGG repeat forms a triplex in vitro , and stalls replication occurring only when AAGGG serves as the template strand ( 57 ), indicating non-B DNA-forming potential of the pathogenic repeat in RFC1 during DNA replication results in fork stalling. However, no reductions in RFC1 mRNA and protein levels have been observed in peripheral tissues, postmortem brain samples, and induced pluripotent stem cell–derived neurons from patients with biallelic (AAGGG) exp in the RFC1 ( 8 , 58 ). In the aspect of GOF hypotheses, RNA foci were not detected in patient brains in the initial analysis ( 8 ), but in a recent report, CCTGT- and CCCTT-containing RNA foci were identified in the neuronal nuclei of patients with CANVAS harboring biallelic (ACAGG) exp and (AAGGG) exp , respectively ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that pathogenic AAGGG repeat forms a triplex in vitro , and stalls replication occurring only when AAGGG serves as the template strand ( 57 ), indicating non-B DNA-forming potential of the pathogenic repeat in RFC1 during DNA replication results in fork stalling. However, no reductions in RFC1 mRNA and protein levels have been observed in peripheral tissues, postmortem brain samples, and induced pluripotent stem cell–derived neurons from patients with biallelic (AAGGG) exp in the RFC1 ( 8 , 58 ). In the aspect of GOF hypotheses, RNA foci were not detected in patient brains in the initial analysis ( 8 ), but in a recent report, CCTGT- and CCCTT-containing RNA foci were identified in the neuronal nuclei of patients with CANVAS harboring biallelic (ACAGG) exp and (AAGGG) exp , respectively ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the aspect of GOF hypotheses, RNA foci were not detected in patient brains in the initial analysis ( 8 ), but in a recent report, CCTGT- and CCCTT-containing RNA foci were identified in the neuronal nuclei of patients with CANVAS harboring biallelic (ACAGG) exp and (AAGGG) exp , respectively ( 59 ). Both AAGGG repeat-RNA foci and CCCTT repeat-RNA foci were detected in control and CANVAS patient induced pluripotent stem cell–derived neurons, but the overall abundance of foci was low and the specificity was incomplete ( 58 ). In RAN translation, AAGGG repeat–derived KGREG peptide products were selectively detected within cerebellar granule cells in CANVAS patients, with no signal detected in controls ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies propose that RFC1 loss-of-function could be at the basis of the repeat expansion pathogenicity 20-23 , as the recessive inheritance pattern also suggests. However, other studies showed no specific neurodegenerative phenotype in RFC1 -depleted neuronal cultures in vitro 24 . This questions the direct involvement of the RFC1 gene in so-called RFC1 -related pathologies.…”
Section: Introductionmentioning
confidence: 89%
“…Cells were regularly passed and the media replenished every 3 days. Dermal fibroblasts were obtained from consenting patients clinically diagnosed with CANVAS spectrum disorder and genetically confirmed to possess biallelic RFC1 expansions and iPSCs were cultured as described in Maltby et al (35). ALS patient fibroblasts originated from a 66 yo male Michigan Medicine patient and obtained as skin biopsy punch under local IRB approval (HUM00030934).…”
Section: Cell Culturementioning
confidence: 99%